Сказки лесной опушки - Бианки Виталий Валентинович (Родничок, 2009)
Экземпляры: ф.3 (2011) / Инвентарный номер: 53871 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 59 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4